2023
DOI: 10.1007/s00395-023-01000-6
|View full text |Cite
|
Sign up to set email alerts
|

The heterocellular heart: identities, interactions, and implications for cardiology

Abstract: The heterocellular nature of the heart has been receiving increasing attention in recent years. In addition to cardiomyocytes as the prototypical cell type of the heart, non-myocytes such as endothelial cells, fibroblasts, or immune cells are coming more into focus. The rise of single-cell sequencing technologies enables  identification of ever more subtle differences and has reignited the question of what defines a cell’s identity. Here we provide an overview of the major cardiac cell types, describe their ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 223 publications
0
13
0
Order By: Relevance
“…The formation of carotid artery plaques involves excessive lipid deposition, endothelial damage, and inflammatory immunocyte infiltration at the lesions, [32][33][34] while heart diseases encompass malfunctioning cardiomyocytes, fibroblasts, and imbalanced immune activities in response to intrinsic or extrinsic (eg, ischemia, valvular defects) triggers. [35][36][37] Overall, our data manifest that the DNMT3A and TET2 mutations associate with inflammatory macrophages in both cardiovascular tissues.…”
Section: Discussionmentioning
confidence: 60%
“…The formation of carotid artery plaques involves excessive lipid deposition, endothelial damage, and inflammatory immunocyte infiltration at the lesions, [32][33][34] while heart diseases encompass malfunctioning cardiomyocytes, fibroblasts, and imbalanced immune activities in response to intrinsic or extrinsic (eg, ischemia, valvular defects) triggers. [35][36][37] Overall, our data manifest that the DNMT3A and TET2 mutations associate with inflammatory macrophages in both cardiovascular tissues.…”
Section: Discussionmentioning
confidence: 60%
“…The heart contains heterogeneous subsets of resident macrophages [ 6 , 16 , 17 , 42 ]. Having discovered that MR deletion prevents macrophage polarization toward a pro-inflammatory phenotype in the aging heart, we next determined whether there were associated changes in the number and proportion of macrophage subsets.…”
Section: Resultsmentioning
confidence: 99%
“…Resident macrophages are gatekeepers of tissue homeostasis and integrity and prime cells involved in initiation and regulation of inflammatory responses [ 5 , 61 ]. Heterogeneous populations of macrophages deriving from embryonic progenitors as well as bone marrow precursor cells co-exist in the heart [ 6 , 42 ]. Age-dependent alterations in the cardiac microenvironment and intrinsic dysregulations can lead to phenotypic and functional changes in resident macrophages that could have profound effects on cardiac aging [ 32 , 34 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…The heart is composed of numerous cell types that show distinct gene expression profiles [ 30 ]. To assess the impact of catecholamine treatment on cardiomyocyte gene expression, mRNA expression in isolated cardiomyocyte nuclei was determined by RNA-seq (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the underlying molecular mechanisms involved in that process, we studied the transcriptional response to IsoPE in cardiomyocytes. This approach allowed us to decipher the regulation of signaling pathways within a given cell type in a less biased manner compared to the analysis of cardiac tissue [ 27 , 30 , 38 ]. Studies comparing the effects of combined IsoPE treatment to isoprenaline alone indicated that concurrent activation of α-adrenergic receptors enhances the effect of isoprenaline on cardiac remodeling and gene expression [ 15 , 35 ].…”
Section: Discussionmentioning
confidence: 99%